Peningkatan Performansi Benih Kedelai Edamame (Glycine max L. Merrill.) yang Telah Mengalami Deteriorasi melalui Metode Priming - Dani Triyadi; Ari Wahyuni; Nurman Abdul Hakim; Gut Tianigut (Planta Simbiosa, 2023)
One of the essential factors in edamame soybeans production is the use of quality soybean seed. Quality seeds had high viability and vigor values. One of the problems faced in the supply of quality seeds is seed deterioration. Seed deterioration is a process of decreasing seed vigor and viability during storage. Priming is a seed invigoration technique which is a process that controls the hydration-dehydration of seeds for metabolic processes to take place before germination. This objective was to determine the effect of priming media on the viability and vigor of edamame soybean seeds. This study was carried out from November 2021 to January 2022Â  in the Seed Technology Study Program greenhouse, Politeknik Negeri Lampung. This study used a factorial Completely Randomized Design (CRD) consisting of two treatment factors. The first factor consisted of four soaking media, specifically K1 = Aquadest, K2 = ã€–GAã€—_3, K3 = coconut water, and K4 = Atonik. The second factor is soaking time (L), which consists of L1 = 4 hours, L2 = 8 hours, and L3 = 12 hours. The observed variables in this study were germination, vigor index, maximum growth potential, growth simultaneity, growth speed, and root length. The interaction between priming treatment and soaking time had a very significant effect on the germination rate (DB), maximum growth potential (PTM), and growth simultaneity (KST). Meanwhile, the growth speed (KCT), vigor index (IV), and root length (PA) had no significant effect. The best invigoration priming treatment is coconut water as a medium with a soaking time of 12 hours which has the highest value.